Aplikasi Pendataan dan Pelanggaran Administratif Lembaga Pemasyarakatan (LP) Kelas IIA Kota Banjarmasin Berbasis Web - Mustafa Kamaludin (mijournal.org, 2025)
The processing of visitor data, inmates, and administrative violations in Class IIA Penitentiary (LP) of Banjarmasin City has been conducted manually and semi-computerized, resulting in inefficient and inaccurate reporting. Furthermore, the absence of a security system leaves the data vulnerable to unauthorized manipulation. This research develops a web-based application to manage visitor and inmate data using the Waterfall development model. The system design uses a context diagram and Data Flow Diagram (DFD). The tools used include Sublime Text 3 and XAMPP 3.2.2 with PHP and MySQL. The resulting application is expected to help staff manage data quickly, effectively, and efficiently.